Expanded newborn screening for inborn errors of metabolism and genetic variants in Xinjiang, China - Huiwen Zhang; Haoyue Tian; Wencheng Dai; Luhan Zhang; Gang Guo; Guifeng Ding (Frontiers in Genetics)
Inborn errors of metabolism (IEMs), with diverse clinical phenotypes, are featured primarily by complex etiology, lack of specificity in clinical manifestations, major damage to the nervous and digestive system, and even death, bringing great pain and economic burden to children and families. Expanded newborn screening for IEMs by tandem mass spectrometry (MS/MS) is effective to realize early diagnosis and presymptomatic treatment, which may be useful for preventing severe permanent sequelae and death. This study was scheduled to determine the disease spectrum, prevalence and gene variants of IEMs in Xinjiang, China. A sum of 107,741 newborns were screened by MS/MS from January 2019 to December 2024. After initial screening, 3947 newborns, who had positive results, needed to be recalled. The number of successful recalls was 3817 and the recall rate was 96.71%. Suspected positive patients were further diagnosed through next-generation sequencing (NGS) and validated by sanger sequencing. Seventy-three patients were diagnosed with IEMs in Xinjiang, resulting in an overall incidence of 1/1,476. The incidence of amino acid, organic acid, and fatty acid metabolic disorders were 1/1995, 1/8978 and 1/15392, respectively. Hyperphenylalaninemia, Hypermethioninemia and Methylmalonic acidemia ranked the top 3 of all detected IEMs. One hundred twenty-seven mutations in eleven IEMs-associated genes were identified in 69 confirmed cases. Several hotspot mutations in the PAH gene were identified. This study observed some unreported mutation sites in MAT1A gene, which enriched the gene database. Therefore, our data clearly elucidated the disease spectrum and genetic variants in Xinjiang, contributing to the treatment and prenatal genetic counseling of these disorders in this region.